Characterizing non-similar analysis for chemically reactive magnetized Sutterby bidirectional fluid flow capturing features of non-linear thermal radiation - Khan, Waqar Azeem; Hussain, Zubair; Radwan, Neyara; Ali, Mehboob; Jamal, Nargis (Journal of radiation research and applied sciences, 2024)
In the field of engineering, manufacturing industry, biologically-inspired propulsion systems, augmenting conventional fluid heat-transfer, moisture and drying the chemical reactions are getting the utmost importance. In the last few decades, the study of non-linear materials has attracted a lot of attention in the realm of science. These fluids have importance in food industry, plastic thawing, material processing, pharmaceutical goods, polymeric liquids, biochemical engineering, toxic, nuclear plants, furthermore the mechanical applications, and polymeric liquids promote the investigation of these fluids. The characteristics of three-dimensional Sutterby fluid flow on a bidirectional expansion surface in the context of heterogeneous homogeneous processes have been explored in the current research article. Here in this work, we used an improved heterogeneous homogeneous reactions model with the same diffusion of the reactant and autocatalytic. In addition, heat transfer analysis is performed in the existence of non-linear thermal radiation and convective boundary conditions. By using a suitable similarity approach we reduced the introduced basic non-linear problem in to a self-similar form. Subsequently, the extended non-linear problem was systematically handled employing the BVP4C approach. We also investigated the influence of the related physical parameters on the profiles of concentration and temperature. The graphs demonstrate how a rise in the homogeneous process parameter causes the concentration distribution to drop concurrently with an increase predicated on the Schmidt number. Furthermore, the estimates of the Prandtl number are observed to grow with the rate of surface heat transfer.